Digital imaging and radiographic practise in diagnostic radiography: An overview of current knowledge and practice in Europe. Issue 2 (May 2018) - Mc Fadden, S.; Roding, T.; de Vries, G.; Benwell, M.; Bijwaard, H.; Scheurleer, J.
Abstract: Introduction: Recent research has identified the issue of 'dose creep' in diagnostic radiography and claims it is due to the introduction of CR and DR technology. More recently radiographers have reported that they do not regularly manipulate exposure factors for different sized patients and rely on pre-set exposures. The aim of the study was to identify any variation in knowledge and radiographic practice across Europe when imaging the chest, abdomen and pelvis using digital imaging. Methods: A random selection of 50% of educational institutes (n = 17) which were affiliated members of the European Federation of Radiographer Societies (EFRS) were contacted via their contact details supplied on the EFRS website. Each of these institutes identified appropriate radiographic staff in their clinical network to complete an online survey via SurveyMonkey. Data was collected on exposures used for 3 common x-ray examinations using CR/DR, range of equipment in use, staff educational training and awareness of DRL. Descriptive statistics were performed with the aid of Excel and SPSS version 21. Results: A response rate of 70% was achieved from the affiliated educational members of EFRS and a rate of 55% from the individual hospitals in 12 countries across Europe. Variation was identified in practice when imaging the chest, abdomen and pelvis using both CR and DR digital systems. There is wide variation in radiographer training/education across countries. Conclusion: There is a need for standardisation of education and training including protocols and exposure parameters to ensure that there is continued adherence to the ALARA principle. Highlights: There is great variation in the education and qualifications of staff across Europe. Variation exists in the standard operating parameters used in Digital Radiography. There is a need for standardisation of protocols and exposure parameters at national and international level. Further education of all technical factors relating to patient dose and image quality in Digital Radiography is required.